Numerical Algorithms : Methods for computer vision, machine learning, and graphics - Solomon, Justin (Boca Raton : CRC press, 2025)
This text presents a new approach to numerical analysis for modern computer scientists. Using examples from a broad base of computational tasks, including data processing, computational photography, and animation, the book introduces numerical modeling and algorithmic design from a practical standpoint and provides insight into the theoretical tools needed to support these skills. Comprehensive end-of-chapter exercises encourage critical thinking and build students$1 (Bintuition while introducing extensions of the basic material.s
Includes Bibliography and index
Keywords: Nonlinear Systems; Eigenvectors; Numerics and Error Analysis; Column spaces and QR